Development of aluminium air seawater battery - Maziati Akmal Mohd Hatta (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
The feasibility of aluminium-air seawater battery as potential power source for marine applications is investigated. The cell, measuring 20 mm x 30 mm, comprises of an aluminium anode and laminated sheet of E4 air electrode. Two cell designs are studied i.e. the enclosed and open configurations. The electrolyte used is sodium chloride (0.5 M and 4 M) and seawater. Sodium chloride (NaCl) electrolyte of 0.5 M is used as a substitute for seawater while that of 4 M possesses the highest electrolyte conductivity. The open configuration design mitigates the electrolyte and heat management issues, and hence enhances the cell discharge performance markedly. The open configuration cell, however, prevents the serial cell arrangement. As such, the cell design needs to be optimized in order to increase its performance. It is discovered that, the key design element is the air electrode. Merely by adopting multi-polar air electrode design, the energy output of Al-air seawater cell is extended from 173 mWh to 779 mWh (rated at 1 mA), a significant improvement factor of 4.5. Generally, as the rating current is doubled, the energy output will be halved. Besides, other design aspects that could be implemented to improve the discharge performance are using parallel stacks arrangement and scaling up the cell size. The parallel twin-stack cell extended the discharge duration from 11 days to 26 days, also rated at 1 mA. On the other hand, the fourfold increment of the electrodes' size from 20 mm x 30 mm to 40 mm x 60 mm would double the energy output. The electrochemical reactions of Al-air seawater cell are established from the physical characterizations of X-ray diffraction and cyclic voltammetry. Taking into account the parasitic corrosion of aluminium electrode in seawater, the anodic efficiency of the Al-air cell is estimated around 79 %.